D'Arcy Thompson's 'on Growth and form': From soap bubbles to tissue self-organization. (June 2017) - Heisenberg, Carl-Philipp
Abstract: Tissues are thought to behave like fluids with a given surface tension. Differences in tissue surface tension (TST) have been proposed to trigger cell sorting and tissue envelopment. D'Arcy Thompson in his seminal book 'On Growth and Form' has introduced this concept of differential TST as a key physical mechanism dictating tissue formation and organization within the developing organism. Over the past century, many studies have picked up the concept of differential TST and analyzed the role and cell biological basis of TST in development, underlining the importance and influence of this concept in developmental biology.